2016
DOI: 10.1097/acm.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Does Time Pressure Have a Negative Effect on Diagnostic Accuracy?

Abstract: Time pressure has a negative impact on diagnostic performance. The authors propose that the effect of time pressure on diagnostic accuracy is moderated by both the case difficulty level and the physician's level of experience. Post hoc analyses demonstrated that time pressure affects diagnostic accuracy only if cases are not too difficult and physicians' expertise level is intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…We state this conclusion with some certainty because our study used a within-group design, excluding the possibility of confounding factors due to poor randomization. In addition, we have used the same methodology in similar studies, demonstrating that our procedures are sensitive to experimental manipulations of the kind attempted in this study (23,24). For instance, in a study on the negative influence of so called "difficult patients," using the same methods, we were able to demonstrate rather strong effects with similarly subtle differences in the descriptions of patients (17,18).…”
Section: Discussionmentioning
confidence: 62%
“…We state this conclusion with some certainty because our study used a within-group design, excluding the possibility of confounding factors due to poor randomization. In addition, we have used the same methodology in similar studies, demonstrating that our procedures are sensitive to experimental manipulations of the kind attempted in this study (23,24). For instance, in a study on the negative influence of so called "difficult patients," using the same methods, we were able to demonstrate rather strong effects with similarly subtle differences in the descriptions of patients (17,18).…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the present authors found that the negative effects of time pressure could extend to physicians’ diagnostic performance. Using clinical vignettes, we showed that senior internal medicine residents committed more diagnostic errors when they were put under time pressure compared with a control group . Although these results suggest that time constraints can reduce the quality of diagnosis, other studies did not show this effect, but instead suggested that quick processing does not necessarily lead to diagnostic error…”
Section: Introductionmentioning
confidence: 65%
“…A randomised controlled experiment by ALQahtani et al, for example, reported that internal medicine residents made on average 37% more diagnostic errors under time pressure than their peers in the control no-time-pressure group [22]. Similarly, in a Time pressures faced in general dental practice, therefore, may have a negative impact on the quality of care delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Although dentists perceive time pressure as an important stressor which may potentially influence their clinical decisions [16,17], a systematic review of the dental literature identified no experimental studies that assessed the impact of stress or different stressors on dentists' performance [18]. In contrast, there is ample evidence from other medical domains showing that time pressure affects decision making and diagnostic accuracy of healthcare professionals as well as their psychomotor performance and procedural skills [19][20][21][22][23]. Whether time pressure has similar impact on dentists' performance, however, is an open and important question.…”
Section: Accepted Manuscriptmentioning
confidence: 99%